Design of Tartibtar System In Pmmk Unit Department of Maritime - Nur Rahmani; Zulyani; Handro Okta Prianus (International ABEC, 2022)
The cadets of the Maritime Department of the State Polytechnic of Bengkalis as prospective shipping professional officers who are expected to have personality competencies that need to have good physical and mental conditions, so that all cadets are obliged to obey and comply the rules of maritime cadets. Currently the recording of cadet indiscipline points is still done manually by recording cadets' violation points and monitoring cadet data note in the violation book, therefore supervisors and PMMK members are often confused in finding cadets' personal and historical data, in addition to personal data reports and activity reports. cadets that should besubmitted to Academic advisors andcadets' families are often reported late because it takes a long time. To assist the performance of the cadet moral and discipline building unit in handling problematic students, therefore we need an application that functions as an information system and decision support system that aims to facilitate the performance of PMMK in order to document data, monitor, and provide appropriate further action. The purpose of this research is to design a computerized system in the Tatibtar application for checking application that can accommodate information and present quickly, precisely, and accurately about the state of the cadet point record. This application is implemented properly and correctly and is expected to minimize the human error factor. Make it easy to control input and output data in presenting information about the credit status of cadet points so that it can be done quickly and can be accessed by cadets, parents, and campus parties in the maritime department. The application is a decision support system can assist related parties in the results of the implementation of the task of supervision and enforcement of student discipline quickly and precisely.